THE QUALITY OF LIFE OF CHILDREN WITH ESSENTIAL ARTERIAL HYPERTENSION - D.I. Sadykov; I.Ya. Lutfullin (Педиатрическая фармакология)
The quality of life of adolescents aged 14 to 17 with essential arterial hypertension has been studied using the questionnaire MOS SF-36. The results of the study indicate a significant drop in both mental and physical health of adolescents. It has been established that the level of arterial blood pressure is not the only factor determining a deteriorated quality of life of adolescents with essential arterial hypertension. A deterioration in the quality of life is most characteristic of adolescents with labial arterial hypertension: this was found on all of the 8 scales in the questionnaire. In adolescents with stable arterial hypertension, a definite reduction in the quality of life was revealed only on six out of 8 scales examined. Physical activity in adolescents both with stable and labial arterial hypertension was limited to the same extent, however, psychoemotional stress was more common in adolescents with labial arterial hypertension. In the authors’ view, the revealed differences indicate the different extent to which psychosomatic mechanisms are involved in the development of arterial hypertension and a need for tailor-made approach to treating this category of adolescents.Key words: the quality of life, essential arterial hypertension, adolescents.